Black entrepreneurship: A multilevel process model of constrained agency across the business venturing lifecycle - Lewis, Trey; Hunt, Richard A.; Murphy, Maurice J.; Townsend, David M. (Journal of Business Venturing, 2026)
Black entrepreneurship (BE) plays an increasingly important, and increasingly paradoxical, role in contemporary American society. On one hand, BE is a vehicle for economic advancement, exemplified through inspiring instances of resolute agency, heroic achievement, and storied successes that collectively reinforce the notion that entrepreneurship can be a potent, emancipatory force of social and economic mobility. On the other hand, BE is also a vivid illustration of race-related challenges, chronicled through an abundance of empirical evidence that reveals the extent to which Black entrepreneurs navigate a racialized entrepreneurial context; one in which formidable constraints arise throughout the entrepreneurial journey. Though critically important, the mechanisms of racialization – and the manner in which they are manifested and surmounted – remain under-theorized, leading to an incomplete understanding of how and why success is more elusive for historically marginalized entrepreneurs than it is for others, and why the threat of failure looms so large. To address these research challenges, we build upon existing work to develop a process model, depicting the unique constraints that Black entrepreneurs face at each stage of the business venturing lifecycle. Applying this processual perspective, we articulate a theory of constrained agency, wherein Black entrepreneurs can and do exercise entrepreneurial agency despite varying, multilevel manifestations of racialization. Our work lays the groundwork for a more detailed, purposeful, and relevant approach to the future research of Black entrepreneurs as well as other historically marginalized groups.